Implementasi HOT-Fit Model Dalam Evaluasi Perpustakaan Digital Universitas PGRI Madiun - Ridho Pamungkas (LPPM Universitas Merdeka Madiun, 2019)
The library is a Technical Implementation Unit in tertiary institutions that has a role as a means of supporting the lecture process for students as well as media for gathering and disseminating information in the aspects of education, research aspects and aspects of community service to help achieve the Tri Dharma of Higher Education. Digital Library is the result of the role of information technology that provides convenience in providing information to users without being hindered by time and space. The aim of this research is to evaluate the digital library of Madiun University using the HOT-Fit Model (Human, Organizaton, Technology) method, which contains several variables, namely system quality, service quality, information quality, service use, service quality, system benefits and customer satisfaction . the results of this study as a whole can be seen the relationship between the three variables interplay between variables.